WORKSHOP IMPLEMENTASI SISTEM MONITORING DAN KENDALI KUALITAS AIR PADA MEDIA TANAM AQUAPONIK MENGGUNAKAN GAWAI - Indrarini Dyah Irawati; Dadan Nur Ramadan; Sugondo Hadiyoso; Rita Purnamasari; Gelar Budiman; Nurwan Reza Fachrurrozi; Yudiansyah Yudiansyah; Syifa Nurgaida Yutia; Sasmi Hidayatullah Yulianing Tyas; Siti Zahrotul Fajriyah (Universitas Mataram, 2023)
The industrial revolution 4.0 greatly impacts the learning curriculum, especially at the vocational and higher education levels. They are required to play an active role in the success and acceleration of the implementation of industry 4.0. Higher Education becomes a kind of place for preparation or training for human resources (HR) to provide skills that are directly related to the application and development of applications that support industry 4.0. In order to support the government's efforts, the community service team at Telkom University and the Telkom Jakarta Institute of Technology actively participated in collaborating with SMK Nagrak Purwakarta. This community service focuses on bridging productivity between departments in Nagrak Vocational School such as the Food Crops and Horticulture Agribusiness (ATPH) department and the network computer engineering department (TKJ) so as to produce the right cultivation, namely Internet of Things (IoT) based aquaponics. This activity consists of making modules and video tutorials for students and teachers, designing sensors and devices, and making monitoring applications on smartphones to monitor aquaponic plants. The sensor designed consists of a PH detection sensor in the air and an oxygen sensor installed in the school's aquaponics garden. The students and teachers were enthusiastic in participating in workshops regarding IoT materials. Not only getting material, students and teachers then do direct practice to make aquaponics and monitor temperature. Based on a survey of the results of this community service implementation, teachers and students are very satisfied and enthusiastic about and hope that community service activities can be carried out on an ongoing basis.